Successful remission of extensive liver metastases in a breast cancer patient with acute liver failure using a combined chemotherapy regimen with mitomycin, folinate, and 5-Fluorouracil (Mi/Fo/FU) - Stoiber, Natalija; Hauser, Nik; Stoiber, Bernhard; Hohl, Michael K.; Sohn, Christof; Eichbaum, Michael H. R. (Onkologie, 2010)
Background: Liver failure due to disseminated hepatic secondaries represents a therapeutic dilemma in patients with metastatic breast cancer (MBC). Reduced liver function and non-assessable toxicity are limiting factors in the selection of chemotherapeutic agents. Currently, there is no standard treatment after failure of anthracycline-and taxanebased first-line therapies, although there is a variety of well evaluated drugs such as capecitabine. Case Report: We report on a 45-year-old breast cancer patient with disseminated hepatic metastases. She presented in markedly poor condition, showing substantial ascites and extensive jaundice. Blood chemistry analysis showed increased serum levels of liver enzymes (aspartate aminotransferase 271 U/l, alanine transaminase 101 U/l), bilirubin (7.9 mg/dl), and CA 15-3 (1,459 U/l). We induced a palliative chemotherapy with mitomycin, folinate, and 5-fluorouracil (Mi/Fo/FU). The patient improved impressively after the first cycle of systemic therapy. Liver enzymes stabilized continuously, CA 15-3 returned to normal. The patient was discharged 2 weeks after the treatment start. Chemotherapy was well tolerated under dose escalation, no grade 3/4 toxicity was observed. The progression-free interval was 5 months. Conclusions: A combination therapy with Mi/Fo/FU appears to be a reasonable and tolerable alternative salvage strategy for patients with liver failure due to hepatic breast cancer metastases.